Instructional and assessment Strategies Used by the English Teachers in English Language Teaching at Aura Sukma Insani Kindergarten School in Academic Year 2013/2014 - ., Desak Putu Ayu Arsarianti; ., Ni LP. Eka Sulistia Dewi, S.Pd. M.Pd.; ., Prof. Dr. Anak Agung Istri Ngr. Marha (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian deskriptif kualitatif yang bertujuan untuk mengetahui jenis strategi pembelajaran dan strategi evaluasi yang digunakan oleh guru Bahasa Inggris dalam pengajaran Bahasa Inggris di TK Aura Sukma Insani pada tahun ajaran 2013/2014. Dalam penelitian ini, penulis mengobservasi proses belajar mengajar yang dilakukan oleh guru Bahasa Inggris di empat kelas yang berbeda, yaitu A1, A2, B1, dan B2. Data dikumpulkan menggunakan check list observasi dan wawancara yang dianalisis secara deskriptif. Hasil penelitian menunjukkan bahwa ada tiga belas jenis strategi pembelajaran yang diaplikasikan oleh guru Bahasa Inggris anatara lain, TPR, TPR songs and finger-plays, syllable clapping, minimal pairs, drill, dialogue, sticking picture, look and say, connecting vocabulary to young learners’ lives through personalization, what’s missing?, bingo, guessing game, dan song. Sedangkan untuk strategi evaluasi, ada satu jenis yang muncul. Strategi itu adalah nonverbal responses.Kata Kunci : pengajaran Bahasa Inggris, strategi evaluasi, strategi pembelajaran. This study is descriptive qualitative study which aims at finding out kinds of instructional and assessment strategies used by the English teachers in English language teaching at Aura Sukma Insani Kindergarten School in the academic year 2013/2014. In this study, the researcher observed teaching learning process done by the English teachers in four different classes, such as A1, A2, B1, and B2. The data were obtained using observation check list and interview guide and were analyzed descriptively. The result of this study showed that there were thirteen instructional strategies conducted by the teachers, such as TPR, TPR songs and finger-plays, syllable clapping, minimal pairs, drill, dialogue, sticking picture, look and say, connecting vocabulary to young learners’ lives through personalization, what’s missing?, bingo, guessing game, and song. Meanwhile for assessment strategy, there was one strategy which was observable. That strategy was nonverbal responses.keyword : assessment strategy, English language teaching, instructional strategy.